Histopathologic Characteristics of Invasive and Non-invasive Ductal Tumors have Relationship with Different Phenotypes of ER / PR Receptors in Breast Cancer Patients - Golmohammadi, Rahim; Mohajeri, Mohammad Reza; Mosavi Jarrahi, Alireza; Moslem, Ali Reza; Pejhan, Akbar; gohari, Ali (Asian Pacific Journal of Cancer Biology, 2021)
Objective: Contradictory reports have been published regarding the expression levels of the hormone receptors of estrogen and progesterone (ER / PR) and theirclinical importance in diagnosis of breast cancer. The aim of this study was to evaluate the relationship between pathological features of invasive and non-invasive ductal tumors by different ER / PR phenotypes. Methods: This descriptive-analytical study was performed on 74 specimens of breast cancer referred to Isfahan Hospitals for diagnosis between 2015 - 2018. After fixation of the specimens in formalin, tissue passage, cross section and H / E staining, the specimens were divided into two groups: non- invasive and Invasive ductal Carcinoma. After removing of mask, expression of different ER / PR phenotypes was performed using primary monoclonal antibody and immunohistochemically methods. Results: From 74 malignant specimens, 61 (82.4%) were in the category of invasive ductal tumors and 13 cases (17.6%) were in the category of non-invasive ductal tumors. Out of 73 patients with positive ER or PR phenotype 47 samples (63.5%) had ER + / PR +phenotypes, 6 samples had (8.1%) ER+ / PR –phenotype, 20 samples (27%) had ER- / PR + phenotype and only one sample (1.4%) had the ER- / PR- phenotype and was in the category of invasive ductal tumors. There was not detected ER- / PR- phenotype expression in non-invasive ductal tumor. Further analysis showed that there were not significant difference between ER / PR phenotype and tumor stage (p =0.36) or with tumor Grade (P=0.38), high age of menopause or post menopause (P> 0.05). Conclusion: Our data shows that expression of ER- / PR- phenotype only was detected in invasive ductal tumor. It is thought that the tumor type maybe affects the expression of different types of ER / PR hormone receptor phenotypes in breast cancer patients.